Atlas Regeneration Company, Inc. (March 2016) - Makarev, Eugene; Isayev, Olexandr; Atala, Anthony
Atlas Regeneration is dedicated to the development of novel data-driven solutions for regenerative medicine, adapting proven technologies, and analysis strategies to take a multiomics-wide view of stem cell quality and cell fate design. Our core offering is a global comprehensive map of stem cell differentiation, Universal Signalome Atlas for Regenerative Medicine, reflecting the pathway activation states across all characterized stem cells and their differentiated products. Key applications of Universal Signalome Atlas for Regenerative Medicine will include quality assurance for engineered cell products, and directed regeneration pharmacology, where we will screen and identify compounds that can efficiently convert pluripotent cells into desired subtypes. Another marketable piece of IP is development of specialized signaling pathway analysis systems Regeneration Intelligence which supposed to target the unmet needs of determination and prediction of stem cell signaling pathway activation to govern cell differentiation in specific directions.